The Impact of Metformin on Cardiac Troponin-I and ST Resolution in Patients with ST Elevation Myocardial Infarction Undergoing Thrombolytic Therapy - Naser Aslanabadi; Samineh Beheshtirouy; Sina Mashayekhi; Zahra Heidari; Sana Hamedani; Taher Entezari-Maleki (Tabriz University of Medical Sciences, 2023)
Background: Thrombolytic therapy is a key in the management of ST elevated myocardial infarction (STEMI). Metformin implies a series of cardioprotective effects. We aimed to investigate how pretreatment with metformin could affect cardiac troponin I (cTnI) levels following reteplase therapy amid STEMI patients. Methods: A pilot randomized clinical trial was carried out in 80 STEMI patients undergoing thrombolytic therapy with reteplase. The metformin group (n = 40) received a single dose of 1000 mg metformin orally before receiving reteplase, while the control group (n = 40) received only reteplase. The serum level of cTnI was measured at baseline, 8, 16, 24, and 32 hours after the admission to assess myocardial damage. Results: There was no significant difference in cTnI levels at baseline (p = 0.657), 8 (p = 0.93), 16 (p = 0.690), 24 (p = 0.217), and 32 (p = 0.517) hours after STEMI diagnosis between two groups. The mean differences were also not significant for changes of cTnI at baseline and other time frames. Conclusion: The results of the present study demonstrated that early use of 1000 mg metformin prior to reteplase could not reduce the level of cTnI in STEMI patients.